2007
DOI: 10.1177/0269216307083033
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and place of death for the elderly: a 10-year population-based study

Abstract: After adjusting for other socio-demographic, clinical and healthcare factors, the place of death has a significant association with the level of urbanization among the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
(46 reference statements)
2
22
0
3
Order By: Relevance
“…The 359 communities in Taiwan were classified into 7groups: highly urbanized area, moderately urbanized area, boomtown, general town, aging town, agricultural town, and remote town. This classification method has been used in several studies [48][50].…”
Section: Discussionmentioning
confidence: 99%
“…The 359 communities in Taiwan were classified into 7groups: highly urbanized area, moderately urbanized area, boomtown, general town, aging town, agricultural town, and remote town. This classification method has been used in several studies [48][50].…”
Section: Discussionmentioning
confidence: 99%
“…12 With regard to the area of residence, few studies have analyzed the influence that it has on the place of death. 13 However, these studies have shown that the level of urbanization influences the place of death, with hospital deaths being associated with a better level of urbanization. Our result of death in home for people living in rural areas is consistent and could be explained by the fact that in rural areas there is a lack of health care services.…”
Section: Discussionmentioning
confidence: 99%
“…This variable also controls for regional differences in palliative care and chaplaincy services [37-39]. Population density was included as a control variable in the analyses because it also has been found to be related to the rate of hospital deaths [17,18,22]. The AHA survey measures population density on a 0-6 scale, reflecting the size of the Metropolitan Statistical Area in which a hospital is located.…”
Section: Methodsmentioning
confidence: 99%
“…Research in Belgium [10], Germany [17], and Taiwan [18] has shown that people living in urban areas are more likely to die in the hospital than those living in rural areas, although findings from other studies are inconsistent [2,7]. The observed relationship between hospital deaths and population density, as well as the regional differences, may be partly attributable to the number of available hospital beds per capita, with areas that have a greater number of hospital beds per person having higher rates of hospital deaths [3,19].…”
Section: Introductionmentioning
confidence: 99%